(3GNJUGQ TQM GdHfGfj Ydj NWHI CdajI GHf eGdcs - (3MeOhf Hf eMeO HfGfj Hf YHO GdSdGes
(3ChdgG (B:s
(3hHYO, ajbhd MeOhf Hf eMeO HfGfj Hf YHO GdSdGe deG cGf TQM NGdfG YHOGddg SjOj eMeO Hf eMeO Hf MeOhf HfGfj s
(3BNQgG (B:s
(3fhY ef CfhGY GdHOjY hgh MSf GdGfJgGA dCf GdNJe HGdOYGA eYghO ddHdZGA, cbhdg HbjJ HbGA GdOgQ hgPG OYGA ddHQjI TGed hgPG BNQ GdGNJUGQ s
(3fSNI KGfjIs
(3JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa jSjQ aj HYV GdCdaGXs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs